Prospects of Higher Education System (on the example of Uzbekistan) - Rashit Baratov (International Journal on Orange Technologies, 2021)
Today, Uzbekistan's rapid implementation of large-scale reforms in all spheres is directly related to the fact that it is continuously being filled with mature staff. On the way, promising programs are being created in the country, and it is being implemented on the basis of today's requirements. This article analyses the new approaches in the system of personnel training in Uzbekistan